Environmental contamination due to arsenic and its effects on livestock system - ROY, M; PANDEY, P K; ROY, S; MISRA, S (The Indian Journal of Animal Sciences, 2011)
Epidemiological study was undertaken to access the status of arsenic status in the ruminants of some parts of centraleast India, which are geologically enriched with arsenic. Major biomarkers, viz. hair, were used to assess the environn1ental exposure of arsenic in ruminants. Owing to the relatively short life span of rUlninants the external lesions of arsenicosis were not observable yet, the presence of toxic levels of arsenic in the body fluids like blood, urine, were detected. Among the various species, caprines showed highest concentration of arsenic and consequent signs of toxicity. Significantly higher arsenic residues were recorded in tail-hairs of animals reared around contaminated sites compared to the control. A food basket analysis was also carried out. Food and water consumed by animals and humans of the arsenic contaminated regions were responsible for the development of arsenicosis. Â